Community empowerment for economic improvement through Grenden Nature Tourism - Farida Farida; Aprilia Listyani; Maya Dwi Anggraeni; Faishal Rafli Farhanditya; Nurul Muzdalifah; Rizqiana Barokah (Universitas Muhammadiyah Magelang, 2022)
Community service in the form of increasing the economy through Grenden tourism aims to increase public awareness by jointly building Grenden Nature Tourism to be known by public. This activity is carried out by training in human resources in managing tourism sites, training in allocating human resources, and assisting in the use of social media. The methods are mentoring and empowerment. The result of this service is that the community is quite understand to promote the tourism destination through digital marketing, the improvement of human resources quality and repairing the photo spots in Grenden tourism to increase tourist attraction.